Effects of supplemental energy and protein on forage digestion and urea kinetics in beef cattle - Bailey, Eric Arthur (Kansas State University, 2010)
Two experiments quantified effects of supplemental protein and energy on forage digestion and urea kinetics in beef cattle. In experiment 1, energy treatments included: control, 600 g glucose dosed ruminally once daily, and 480 g VFA infused ruminally over 8 h daily. Casein was dosed ruminally once daily (120 or 240 g). Cattle (208 kg) had ad libitum access to low-quality hay (5.8% protein). Infusion of VFA decreased forage intake by 27%. Glucose decreased NDF digestibility. Microbial N flow was greater for 240 than for 120 g/d casein, but was not affected by energy. Retained N increased with casein supply. Urea-N entry rate (UER) and gut entry of urea-N (GER) were not affected by energy, casein, or interactions, but GER/UER was less when 240 rather than 120 g/d casein was provided. Compared to VFA, glucose tended to increase GER/UER. Glucose led to more microbial uptake of recycled urea than VFA. In these young calves, changes in N and energy supply did not greatly impact urea kinetics, likely because increased N was largely retained. In experiment 2, treatments included: 0 or 1.2 kg glucose, and 240 or 480 g casein. Cattle (391 kg) were fed low-quality hay (4.7% protein). Glucose reduced forage intake by 18%, whereas casein did not affect it, and depressed fiber digestion. Microbial N flow to the duodenum and retained N increased as casein increased, but neither was affected by glucose. Increasing casein increased UER 50%. Urinary urea-N increased as casein increased; moreover, GER numerically increased 25% as casein increased. GER/UER decreased as casein increased. Glucose decreased urinary urea, but did not change UER or GER. Microbial uptake of recycled urea was least for steers receiving 480 g/d casein with no glucose, reflecting that this treatment exceeded ruminal requirement for N. In these more mature steers, increases in N intake increased UER, reflecting that only small proportions of the increased N intake were retained. Thus, as steer maturity increased, UER and GER increased, likely because less N was retained. These studies demonstrate the influence of urea recycling in meeting N needs of cattle fed low-quality forage.
Keywords: Beef Cattle; Urea Kinetics; Agriculture, Animal Culture and Nutrition (0475)